Students' perception towards literature in improving their English language proficiency / Che Nor Aziah Mohamed - Mohamed, Che Nor Aziah (2006)
This research was conducted to study the perception of the students towards literature in improving their English Language proficiency. A survey was conducted at SMK Ibrahim Fikri, Kuala Terengganu to elicit information of the students' perception towards literature in improving their language proficiency. A total of 50 students were selected at random as the respondents in this study. The instruments employed were mainly a questionnaire which comprised of a Likert five point scale ranging from strongly agree to strongly disagree. An informal interview with five teachers were also conducted to support the data. All the data collected were analysed using the frequency count technique and percentages. Then a descriptive analysis of the results were made. The findings indicated positive responses from the students towards literature in improving their English Language proficiency. Learning literature has made their learning of English more enjoyable and their interest in literature tend to be determined by how it was taught and the type of text used. Majority of the students agreed that learning literature has benefited them in some ways in improving their language proficiency in terms of speaking and writing. Finally, it is hoped that the recommendations in this study will assist the relevant stakeholders to select suitable materials for the literature component in English Language syllabus. The introduction of literature is definitely a positive step towards improving English Language among students in schools.